Enablers and barriers to the realisation of an age-friendly environment in Malaysia: a thematic review/ Noorlailahusna Mohd Yusof and Suziana Mat Yasin - Mohd Yusof, Noorlailahusna; Mat Yasin, Suziana (Universiti Teknologi MARA, Perak, 2023)
One of the best ways to support the quality of life for older populations is by promoting an age-friendly environment. Older people must have access to quality healthcare and support systems to remain in the community when they decide to live alone. Thus, a literature review aimed at exploring the enablers and barriers to realising an age-friendly environment for older people is required to understand the modifications needed to adapt to such an environment to support the older populations in Malaysia. The thematic analysis resulted in two themes: (i) the elements of an age-friendly environment in Malaysia and (ii) the enablers and barriers to creating an age-friendly environment. This study enlightens the need for an agefriendly environment and allows for targeted policies and interventions to promote age-friendly features in the living environment, efficiently addressing the challenges of our ageing society. The study also adds to the body of knowledge by providing valuable insights into creating supportive environments for older individuals and fostering their overall well-being.